Inheritance Right of the partner in the stable union, in particular, when he competes with the ascendants (Research, Society and Development, 2022)
This article aims to clarify the succession law of the partner in the stable union, in particular, the competition of this with the ascendants. In order to do so, the issue of the stable union is addressed, that is, if it is considered a family entity and how it is treated under the Civil Code of 2002. Subsequently, the inheritance law came to the fore, an occasion that explains the foreseen setback. in article 1,790 of the Civil Code of 2002, in view of the flagrant discrimination of the partner against the spouse, when the subject is succession. For this reason, the Federal Supreme Court judged Extraordinary Appeals No. 646.721/RS and No. 878.694/MG, resulting in the equalization of the partner to the spouse, applying to both the succession regime provided for in article 1,829 of the Civil Code. However, the Federal Supreme Court left gaps in the judgment, since it was silent on the inclusion of the partner in the list of necessary heirs, provided for in article 1,845. Then, it discusses the competition of the surviving companion with the ascendants of the de cujus. The methodology used is deductive research, through bibliographic and jurisprudential research, decisions of the Federal Supreme Court, legislation and internet journals. Finally, it is concluded that the position of the Federal Supreme Court in the case brought legal certainty to the many couples who today live in a stable union, correcting the setback provided for in article 1,790, with due equivalence between partner and spouse in the law succession.